Investigation of rust formation on steel exposed in heavy industrial environment / Rosly Pengiran - Pengiran, Rosly (2002)
The purpose of this project is an exposure for engineering students to perform on site investigation and analytical jobs regarding rust formation on steel structures exposed in heavy industrial environment. It also gives and understanding about the aggressiveness of the industrial environment against metal, especially steel. Investigation and observation was done within Shah Alam industrial area, where the result and findings are tabulated. An analysis was done base on the result and findings, and further analysis was done with relates all the findings with the related source that quite similar with the field of studies. From the site investigation, many steel structures was found rusted and it is mainly caused by the industrial emission and other factors. The environmental data and others information regarding the Shah Alam industrial area, very much assist in an investigation of rust formation on steel exposed in an industrial environment. Corrosion map have been mapping for future references and applications, where applicable.